2017
DOI: 10.1016/j.ultsonch.2016.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Drastic acceleration of fibrillation of insulin by transient cavitation bubble

Abstract: Amyloid-fibril formation of proteins can be accelerated by ultrasonic irradiation to the peptide solutions. Although this phenomenon contributes to understanding pathogenic behavior of amyloidosis, its physical mechanism has not been clarified, because several factors (cavitation, temperature increase, stirring effect, and so on) related to ultrasonic irradiation can participate in the fibrillation reaction. Here, we independently study contributions of the possible factors, using insulin, which is extremely s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Previous studies 51,52 demonstrated the importance of the liquid-solid interface or the gas-liquid interface as the monomer adsorber; the interfaces dramatically accelerate the aggregation process of amyloidogenic proteins. Furthermore, we previously showed that the shrinking interface highly promotes the nucleation reaction of protein aggregates through the local condensation of the attached proteins, [53][54][55] as illustrated in Fig. S7: Ultrasonic cavitation, i.e.…”
Section: The Evolution Of Oligomer Aggregates Of Aβmentioning
confidence: 99%
“…Previous studies 51,52 demonstrated the importance of the liquid-solid interface or the gas-liquid interface as the monomer adsorber; the interfaces dramatically accelerate the aggregation process of amyloidogenic proteins. Furthermore, we previously showed that the shrinking interface highly promotes the nucleation reaction of protein aggregates through the local condensation of the attached proteins, [53][54][55] as illustrated in Fig. S7: Ultrasonic cavitation, i.e.…”
Section: The Evolution Of Oligomer Aggregates Of Aβmentioning
confidence: 99%
“…Although the effects of agitation may be similar to those of ultrasonication, the cavitation bubbles which lead to the breakdown of supersaturation and ultimately to fibrillation are only generated under ultrasonication. In their comparison of high-speed stirring agitation at 1200 rpm and ultrasonication, Nakajima et al (2017) observed that ultrasonication significantly accelerated the fibrillation reaction.…”
Section: Ultrasonic Power and Strength To Induce Amyloid Fibrillationmentioning
confidence: 99%
“…So et al [28] proposed that fibril formation was mostly limited by the high free-energy barrier, and ultrasound could reduce the high free-energy barrier effectively. Nakajima et al [29] found the transient cavitation bubbles produced by ultrasound accelerated the fibrillation reaction. In summary, it can be referred that ultrasound could regulate protein fibrillation through some specific approaches.…”
Section: Introductionmentioning
confidence: 99%